Mathematical Problem-Solving Ability in Differential Equation - Ari suningsih; Dewi Nopitasari (Basic and Applied Education Research Journal, 2020)
This study aims to describe the student's ability to solve math problems in the Differential Equation course in Polya's steps. This research is a descrip-tive study. The research subjects were the 6th-semester students of STKIP MPL for the 2018-2019 academic year. Data analysis used processed and pre-pared data, read the entire data, analyzed the detail, implemented the coding process, described themes, interpreted the data. The study found that the easy variable differential equation problems could be separated, 2 students understood the problem, 5 students initiated the solution, 4 students com-pleted through the plan, 2 students checked again, 2 students completed through the plan, no students checked again.